NILAI-NILAI PANCASILA DALAM KITAB AL-`ARABIYAH LIL HAYAH SEBAGAI MATERI PEMBELAJARAN BAHASA ARAB: - - Sa`diyah, Halimatus; Wiranegara, Dian Arsitades (Jurnal Pendidikan (Teori dan Praktik), 2023)
Al-`Arabiyah lil Hayah textbook of volume I contains the values of Pancasila which are in accordance with the five principles of Pancasila, namely Belief in the one and only God, just and civilized humanity, The Unity of Indonesia, Democracy guided by the inner wisdom in the unanimity arising out of deliberations amongst representatives, Social justice for the whole of the people of Indonesia. This article aims to find out the Pancasila values contained in the book al-`Arabiyah lil Hayah volume I which was written by the language development center team of UIN Maulana Malik Ibrahim Malang. The book and the material are the main teaching materials for learning Arabic for new students in the Special Program for Arabic Class UIN Maulana Malik Ibrahim Malang. This research includes descriptive qualitative research. The data were obtained through documents in the form of writing and as research sources, namely the book al-`Arabiyah lil Hayah Volume I. The findings from this study are the values of the five principle of Pancasila contained in the book al-`Arabiyah lil Hayah Volume I and only wahdah (chapter) 3 (three) entitled as-sakan (home) does not contain Pancasila values likely because it focuses on Arabic language learning and may not be intended to address broader sociopolitical principles.